Preparation of Silica Gel Grafting Bisquarternary Phosphonium and its Antibacterial Activities - Jin, Dong; Fu, Shihai; Zhang, Fan; Lu, Xiaoping; Han, Pingfang (Asian Journal of Chemistry, 2011)
Using the activate silica gel as a carrier reacted with (3-chloropropyl)trimethoxy silane, the product was early or late reacted with 1,3-bis(diphenylphosphino)propane, 1-chlorotetradecane to give the bisquarternary phosphonium salt water-insoluble antibacterial material. The effect of the reaction temperature, the reaction time and the reaction solvent were studied by means of the orthogonal design method and the single-factor experiment. The optimum conditions are: reaction temperature 150 ºC, reaction time 48 h and the reaction solvent is o-dichlorobenzene. The product has grafted with 0.68 mmol/g phosphonium group and 0.15 mmol/g long alkyl. 1,3-Bis(diphenylphosphino)propane and 1-chlorotetradecane have been early or late grafted to silica gel, characterized by FTIR and TG. The bactericidal rate of the bactericide material was up to 99.9 % using amount of 20 mg/mL in 45 min. The antimicrobial activity of the bactericidal material is still up to 98.7 %, after 5 times repeated usage.